Health economics in the Irish healthcare setting - Walshe, Valerie E. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2008)
Economic analysis plays a key role in deciding which healthcare interventions should be made available in collectively funded healthcare systems. The aim of this thesis is to examine the application of health economics in the Irish healthcare setting. The contribution made by this thesis include the development of: - A cost-of-illness analysis to estimate cardiovascular disease costs from the Irish health service perspective; - A cost-effectiveness model for the eradication of Helicobacter pylori using proton pump inhibitor (PPI) triple therapy in the Irish community setting; - A cost-effectiveness and cost-utility model of statin therapy for the primary prevention of coronary heart disease (CHD) in Ireland; and, - Extensive sensitivity analysis to address uncertainty in the primary prevention statin therapy model.
Keywords: Pharmacoeconomics, Ph.D.; Ph.D. Trinity College Dublin